Badania terenowe nad ukrainskim seksem - Zabuzko, Oksana, 1960-; Kotynska, Katarzyna (Warszawa : W.A.B., 2003)
Polish translation of "Polni vyzkum ukrajinskeho sexu". A novel by the Czech author Oksana Zabuzko.